2022
DOI: 10.1017/jns.2022.34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high nitrate vegetable juice supplementation on plasma nitrate and blood pressure in adults: a pilot randomized crossover intervention in healthy volunteers

Abstract: Beetroot juice (BRJ) has been demonstrated to decrease blood pressure (BP) due to the high inorganic nitrate content. This pilot randomized crossover trial aimed to investigate the effect of two different high nitrate vegetable juices on plasma nitrate concentrations and BP in healthy adults. Eighteen healthy volunteers were randomized to receive 115 ml of BRJ or 250 ml of green leafy vegetable juice for 7 d which contained similar amounts of nitrate (340 mg) daily. Blood samples were collected, and clinic BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For example, a significantly increased plasma nitrate level was found in a healthy adult population after a one-week intake of approximately 340 mg of nitrate through beetroot juice, green leafy vegetable juice, or nitrate-rich vegetables. Moreover, in the same studies, a decrease of SBP and DBP was observed [ 42 , 43 ]. In the same line, plasma nitrate/nitrite levels increased significantly in overweight or obese adolescents after 1 h of intake and after a week of daily intake of 50 g of freeze-dried strawberry powder [ 44 ].…”
Section: Discussionmentioning
confidence: 65%
“…For example, a significantly increased plasma nitrate level was found in a healthy adult population after a one-week intake of approximately 340 mg of nitrate through beetroot juice, green leafy vegetable juice, or nitrate-rich vegetables. Moreover, in the same studies, a decrease of SBP and DBP was observed [ 42 , 43 ]. In the same line, plasma nitrate/nitrite levels increased significantly in overweight or obese adolescents after 1 h of intake and after a week of daily intake of 50 g of freeze-dried strawberry powder [ 44 ].…”
Section: Discussionmentioning
confidence: 65%